Do Places of Delivery Have Contextual Effect on the Perceived Quality of Intrapartum and Postpartum Services? A Multilevel Evidence from Kebumen, Central Java - Helmi Nurlaili; Didik Tamtomo; Bhisma Murti (Journal of Health Policy and Management, 2020)
Background: The maternal mortality rate (MMR) in Indonesia in 2015 was 305 per 100,000 live births. The majority of maternal deaths occur during labor and the puerperium. Increasing access to health services is not enough so that attention is more focused on the quality of services provided. This study aimed to determine the determinants of the quality of childbirth and childbirth by midwives in Kebumen Regency.Subjects and Method: This study was a cross sectional study at 25 health facilities in Kebumen, Central Java, and was conducted during September-October 2019. The study sample consisted of 200 women giving birth and childbirth selected using the proportionate stratified sampling technique. The dependent variable was the quality of childbirth and childbirth services. The independent variables were age, parity, education, occupation, family income, and type of financing. The data collection was performed using a questionnaire and the data analysis was performed using multilevel multiple linear regression with Stata 13.Results: The quality of childbirth and childbirth services increased with maternal age 34 years (b= 1.89; 95% CI = 0.48 to 3.31; p = 0.009), multiparaous (b = 2.20; 95% CI = 0.78 to 3.63; p = 0.002), and type JKN financing (b = 0.27; 95% CI = -0.94 to 1.47; p = 0.659). The quality of childbirth and childbirth services decreased with the education of high education (b= -0.87; 95% CI = -2.02 to 0.28; p= 0.139), working outside the home (b= -1.28; 95% CI= -2.64 to 0.08; p= 0.065), and family income of Rp 1,686,000 (b= -1.85; 95% CI= -3.24 to -0.47; p= 0.009). There was a contextual influence of the place of delivery and postpartum on the quality of services received by mothers with ICC= 51.26%.Conclusion: The quality of childbirth and childbirth services has improved with the age of 34, multiparous, and JKN types of financing. The quality of childbirth and childbirth services declined with the education of mothers who were high school graduates, working outside the home, and family income of Rp1,686,000. There is a contextual influence of the place of delivery and postpartum on the quality of service received by the mother.Keywords: quality of service, childbirth, community health center, multilevel analysisCorrespondence: Helmi Nurlaili. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: helminurlaili@gmail.com. Mobile: 085869950546Journal of Health Policy and Management (2020), 5(1): 23-34https://doi.org/10.26911/thejhpm.2020.05.01.03